Amortizing Rate-1 OT and Applications to PIR and PSI - Chase, Melissa; Garg, Sanjam; Hajiabadi, Mohammad; Li, Jialin; Miao, Peihan (2021 Theory of Cryptography Conference, 2021)
Recent new constructions of rate-1 OT [Dottling, Garg, Ishai, Malavolta, Mour, and Ostrovsky, CRYPTO 2019] have brought this primitive under the spotlight and the techniques have led to new feasibility results for private-information retrieval, and homomorphic encryption for branching programs. The receiver communication of this construction consists of a quadratic (in the sender’s input size) number of group elements for a single instance of rate-1 OT. Recently [Garg, Hajiabadi, Ostrovsky, TCC 2020] improved the receiver communication to a linear number of group elements for a single string-OT. However, most applications of rate-1 OT require executing it multiple times, resulting in large communication costs for the receiver.